Niche overlap in sympatric introduced trout from a southern Patagonian river: evidence from stomach contents and stable isotope analysis - Hune, Matias (2022)
We used a combination of stomach content and stable isotope analyses to assess the trophic interactions and feeding habits of two different salmonid species, brown trout (Salmo trutta) and rainbow trout (Oncorhynchus mykiss) in the Serrano River (Magellan and the Chilean Antarctic Region). We found a high dietary niche overlap, which was supported by Schoener’s index and stable isotopes Bayesian ellipses. The diet was dominated by the amphipod Hyalella spp. in both species. Nonetheless, evidence suggests that O. mykiss has a more generalist feeding strategy than S. trutta. The dietary breadth indices and the isotopic niche area, which were broader for O. mykiss than S. trutta, supported this scenario. This study increases our understanding on the trophic relationships among these introduced trout cohabiting the river and their possible effects in freshwater ecosystems from southern Chile.